Cytosolic glucocorticoid receptor in the testis of Bufo arenarum: Seasonal changes in its binding parameters - Denari, Daniela (2006)
Glucocorticoids (GC) are the hormonal mediators of stress. In mammals, high levels of GC have negative eVects on reproductive physiology. For instance, GC can inhibit testicular testosterone synthesis by acting via glucocorticoid receptors (GR), the extent of the inhibition being dependent on GC levels. However, the eVect of GC on testicular function and even the presence of GR in amphibians are still unclear. The purpose of this work was to characterise testicular cytosolic GR in Bufo arenarum, determining the seasonal changes in its binding parameters as well as the intratesticular localisation. The binding assays were performed in testis cytosol with [3 H]dexamethasone (DEX) and [3 H]corticosterone (CORT). Binding kinetics of DEX and CORT Wtted to a one-site model. Results were expressed as means § standard error. Apparent number of binding sites (Bapp) was similar for both steroids (Bapp DEXD 352.53 § 72.08 fmol/mg protein; Bapp CORT D 454.24 §134.97 fmol/mg protein) suggesting that both hormones bind to the same site. Competition studies with diVerent steroids showed that the order of displacement of [3 H]DEX and [3 H]CORT speciWc binding is: DEX » RU486 » deoxycorticosterone (DOC) > CORT > aldosterone > RU28362 > progesterone >>> 11-dehydroCORT. The aYnity of GR for DEX (Kd D11.2 §1.5 nM) remained constant throughout the year while circulating CORT clearly increased during the reproductive season. Therefore, testis sensitivity to GC action would depend mainly on inactivating mechanisms (11-hydroxysteroid dehydrogenase type 2) and CORT plasma levels. Since total and free CORT are higher in the reproductive than in the non-reproductive period, the magnitude of GC actions could be higher during the breeding season. The intratesticular localisation of the GR was determined after separation of cells by a Percoll density gradient followed by binding assays in each fraction. DEX binds to two diVerent fractions corresponding to Leydig and Sertoli cells. In conclusion, in the testis of B. arenarum GC could regulate the function of both cellular types particularly during breeding when CORT reaches the highest plasma concentration.